2014
DOI: 10.1177/0361684313510152
|View full text |Cite
|
Sign up to set email alerts
|

Polyculturalism and Sexist Attitudes

Abstract: In cultural contexts in which sexist beliefs are considered traditional, shifts toward gender equality represent an example of cultural change. Polyculturalism is defined as the belief that cultures change constantly through different racial and ethnic groups’ interactions, influences, and exchanges with each other and, therefore, are dynamic and socially constructed rather than static. Thus, polyculturalism may involve openness to cultural change and, thereby, would be expected to be associated with lower sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Building on our reasoning for and findings supporting the hypothesis that polyculturalism is associated with lower sexual prejudice, we are currently investigating the association between polyculturalism and sexism (Rosenthal, Levy, & Militano, ). Because endorsement of polyculturalism means focusing on the ways that different racial and ethnic groups have interacted and influenced each other's cultures and therefore cultures are constantly changing, we hypothesized that greater endorsement of polyculturalism would be associated with less sexist attitudes, mediated by greater openness to criticizing elements of one's culture that may promote inequality between men and women.…”
Section: Testing the Association Between Polyculturalism And Sexismmentioning
confidence: 99%
See 3 more Smart Citations
“…Building on our reasoning for and findings supporting the hypothesis that polyculturalism is associated with lower sexual prejudice, we are currently investigating the association between polyculturalism and sexism (Rosenthal, Levy, & Militano, ). Because endorsement of polyculturalism means focusing on the ways that different racial and ethnic groups have interacted and influenced each other's cultures and therefore cultures are constantly changing, we hypothesized that greater endorsement of polyculturalism would be associated with less sexist attitudes, mediated by greater openness to criticizing elements of one's culture that may promote inequality between men and women.…”
Section: Testing the Association Between Polyculturalism And Sexismmentioning
confidence: 99%
“…Across four studies, we have thus far found that greater endorsement of polyculturalism is significantly associated with less sexist attitudes, even while controlling for other important and relevant variables, including colorblindness, conservatism, essentialism (both gender and race), gender, gender identification, multiculturalism, race/ethnicity, racial/ethnic identification, right‐wing authoritarianism, and social dominance orientation. Results also suggest that greater openness to criticizing one's own culture partially mediates the association between greater endorsement of polyculturalism and less sexist attitudes (Rosenthal et al, forthcoming). Moreover, results from a longitudinal study thus far indicate that greater endorsement of polyculturalism at the very beginning of college predicts less sexism about one year later among diverse undergraduates (Rosenthal et al, forthcoming).…”
Section: Testing the Association Between Polyculturalism And Sexismmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, among undergraduates at a diverse university, polyculturalism before starting college prospectively predicted increases in positive intergroup contact and friendship from first to second year of college (Rosenthal & Levy, 2016), supporting the connection between polyculturalism and openness to cross-cultural contact and influence. Other research in the us has found polyculturalism to be associated with less sexism (Rosenthal, Levy, & Militano, 2014) and sexual prejudice -i.e., prejudice toward gay men and lesbian women (Rosenthal, Levy, & Moss, 2012)-, as well as with lower intergroup anxiety and greater belonging among undergraduates at a diverse university (Rosenthal, Levy, London, & Lewis, 2016).…”
Section: Polyculturalismmentioning
confidence: 91%